2006
DOI: 10.1101/gr.4759706
|View full text |Cite
|
Sign up to set email alerts
|

Probing genomic diversity and evolution of Escherichia coli O157 by single nucleotide polymorphisms

Abstract: Infections by Shiga toxin-producing Escherichia coli O157:H7 (STEC O157) are the predominant cause of bloody diarrhea and hemolytic uremic syndrome in the United States. In silico comparison of the two complete STEC O157 genomes (Sakai and EDL933) revealed a strikingly high level of sequence identity in orthologous protein-coding genes, limiting the use of nucleotide sequences to study the evolution and epidemiology of this bacterial pathogen. To systematically examine single nucleotide polymorphisms (SNPs) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 69 publications
(109 reference statements)
2
92
0
Order By: Relevance
“…More sensitive means have subsequently been applied to study the evolution of plasmid pO157. By using pO157 from the Sakai strain as a reference for the resequencing and mapping of pO157 from multiple strains, Zhang et al found that differences between pO157 plasmids ranged from few to many at the SNP level (198). Such results reinforce the idea that SNP analysis can be applied on a plasmid genome scale as a more sensitive means for examining the evolution of closely related plasmid genomes.…”
Section: Ehec and Stec Virulence Plasmidssupporting
confidence: 62%
“…More sensitive means have subsequently been applied to study the evolution of plasmid pO157. By using pO157 from the Sakai strain as a reference for the resequencing and mapping of pO157 from multiple strains, Zhang et al found that differences between pO157 plasmids ranged from few to many at the SNP level (198). Such results reinforce the idea that SNP analysis can be applied on a plasmid genome scale as a more sensitive means for examining the evolution of closely related plasmid genomes.…”
Section: Ehec and Stec Virulence Plasmidssupporting
confidence: 62%
“…coli O157:H7 strains associated with outbreaks and severe epidemicity have been shown to represent a single phylogenetic branch when they are grouped by MLST (using seven housekeeping genes), comprising 100% of the seropathotype A strains (40,50,51). It has been postulated that over the last 50 years, the pathogenic O157 lineage has evolved from an enteropathogenic E. coli O55:H7 group with the acquisition of verotoxin-converting phages and an O157 rfb (O-antigen subunit) gene cluster (3).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge a Department of Homeland Security IAG #224-04-2806 for supporting work on the discrimination of E. [31,32].…”
Section: Acknowledgementsmentioning
confidence: 99%